Cotton Gin Trash: Alternative Roughage Feed for Beef Cattle - Robert O. Myer (EDIS, 2008)
AN-177, a 3-page fact sheet by R. O. Myer, describes the potential use of this cotton ginning by-product as roughage feed for beef cattle. Includes references. Published by the UF Department of Animal Sciences, November 2007.